2018
DOI: 10.1080/1059924x.2017.1423250
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time Elapsed since Last Pruner Maintenance on Upper-Extremity Biomechanics during Manual Flower Cutting

Abstract: Increasing the frequency of pruner maintenance procedures can effectively reduce workers' mechanical exposures during manual flower-cutting operations. Companies should implement daily maintenance programs considering their implementation capacity and expected benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Some studies investigate if and how ergonomic tools and workstations can improve working postures and decrease the risk of MSD with respect to commercial and traditional ones, which are not tailored for specific needs. In general, ergonomic tools and workstations improved postures and comfort and reduced the strain, effort and, consequently, the risk of MSD occurrence and musculoskeletal complaints [ 243 , 251 ]. Better working conditions also resulted in increased productivity and quality [ 253 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies investigate if and how ergonomic tools and workstations can improve working postures and decrease the risk of MSD with respect to commercial and traditional ones, which are not tailored for specific needs. In general, ergonomic tools and workstations improved postures and comfort and reduced the strain, effort and, consequently, the risk of MSD occurrence and musculoskeletal complaints [ 243 , 251 ]. Better working conditions also resulted in increased productivity and quality [ 253 ].…”
Section: Resultsmentioning
confidence: 99%
“…Very few studies did not find FSE in the working tasks [ 117 , 136 ]. Another group of studies identified ergonomic interventions, such as new ergonomic workstations [ 243 ], tools [ 229 ] or training programs [ 239 ] that could be implemented in order to improve the working postures and reduce FSE. Other studies proposed exoskeletons or supporting devices in order to reduce the FSE, especially in prolonged posture maintenance and overhead working tasks [ 259 , 263 ] that require high loads on the neck, back and shoulder [ 261 ].…”
Section: Discussionmentioning
confidence: 99%
“…MSDs in the upper extremities are related to milking tasks, machinery vibrations and fruit harvesting (Colombia, Thailand, Finland, the United Kingdom, USA, Sweden, Italy, Poland, Canada, the Netherlands and Portugal) [125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141].…”
Section: Msd Studies In Agriculturementioning
confidence: 99%
“…The prevention of MSDs and, consequently, the improvement in working conditions render agricultural operations (including livestock, fishing and forestry) more sustainable (India, Brazil, Colombia, Malaysia, Trinidad and Tobago, Iran, Thailand, Algeria, the Philippines, Finland, USA, the Netherlands, Germany, South Korea, Belgium, Portugal, Canada, Italy, France, Sweden, Spain, Poland and Greece) [24,58,87,89,104,107,110,111,114,118,121,124,126,127,140,142,146,148,159,175,184,194,201,209,226,.…”
Section: Msd Studies In Agriculturementioning
confidence: 99%
“…Berrio & Barrero [62] examined the impact of the time passed from the last maintenance of the pruner on the muscular activity and kinematics of the upper extremities for the period of flower-cutting operations. The kinematics of the workers including posture; angular velocity; and acceleration of the forearm, elbow, wrist, and the muscular activity of the upper limbs were evaluated.…”
Section: Pruningmentioning
confidence: 99%